Discovery and characterization of bioactive compounds from endophytic fungi - Gakuubi, Martin Muthee (Nanyang Technological University, 2023)
Fungal endophytes represent a huge resource for the discovery of molecules with greater chemical novelty and interesting bioactivities. Compounds of great therapeutic value such as antibiotics, anticancer, antiviral, antidiabetic and immunosuppressive compounds and those with other industrial and biotechnological applications have been isolated from these largely untapped microbes. However, several factors limit the exploitation of the full biosynthetic potential of these microbial factories. These include, low productivity and titers from native producers, technical barriers associated with endophytic fungi isolation, growth and secondary metabolites (SMs) extraction and the current analytical technology detection threshold. An even greater limitation is the fact that many of the fungal SMs biosynthetic gene clusters (BGCs) are never expressed under conventional laboratory growth conditions. Furthermore, there is also a lack of a versatile genetic engineering system that can be employed across the vast majority of non-model filamentous fungi, making it challenging to fully unravel the biosynthetic capabilities of such fungal strains. The main objective of this study was to evaluate the diversity and bioactive potential of fungal endophytes from A*STAR’s Natural Product Library (NPL) and previously isolated from different habitats of Singapore. We employed bioassay-guided approach to uncover the secondary metabolite synthesizing potential of the study fungal isolates. Furthermore, we assessed the influence of chemical elicitation using two compounds; 5-azacytidine and suberoylanilide hydroxamic acid (SAHA) and variation of fermentation media on the biosynthesis of bioactive fungal SMs. A total of 222 fungal strains were identified on the basis of sequence analysis of ITS2 region of the rDNA gene, with majority (99%; 219 strains) belonging to the phylum Ascomycota while two strains belong to the phylum Basidiomycota, and only one strain was from Mucoromycota phylum. A total of 146 fungal isolates were selected for metabolites extraction following phylogenetic analysis. Chemical elicitation and variation of fermentation media resulted in the discovery of more strains exhibiting inhibitory activities against a panel of microbial pathogens and cancer cell lines. Bioassay-guided isolation and structure elucidation of active constituents from three prioritized fungal strains led to the isolation of palmarumycin C8 and a new analogue palmarumycin CP30 from Lophiotrema sp. F6932. Three new polyketides designated as muyocopronol A - C were isolated from Muyocopron laterale F5912 while a novel 26-membered macrolide designated as tropicicolide was isolated from Colletotrichum tropicicola F10154. Tropicicolide displayed the strongest antifungal activity against Aspergillus fumigatus with an IC50 value of 1.8 μg/mL but with a weaker activity against cthe Candida albicans presenting an IC50 of 7.1 μg/mL. Palmarumycin C8 revealed the best antiproliferative activity with IC50 values of 1.1, 2.1 and 10.7 μg/mL against MIA PaCa-2, PANC-1 and A549 cells, respectively. Biosynthesis of palmarumycin compounds has previously been proposed to involve phenolic oxidative dimerization of 1,8-dihydroxynaphthalene (DHN), the same precursor that is involved in melanin biosynthesis in many filamentous fungi. Thus, we sought to identify and validate the BGC involved in biosynthesis of this group of compounds from Lophiotrema sp. F6932. Whole-genome sequencing analysis resulted in the identification of a putative type 1 iterative PKS (iPKS) predicated to be involved in the biosynthesis of palmarumycins. To verify the involvement of palmarumycin (PAL) gene cluster in the biosynthesis of palmarumycins, we employed ribonucleoprotein (RNP)-mediated CRISPR-Cas9 to induce targeted deletion of the ketosynthase (KS) domain of PAL. Double-strand breaks (DSBs) upstream and downstream of the KS domain were followed by homology-directed repair (HDR) with a hygromycin resistance cassette flanked by a 50 bp of homology on both sides of the DSBs. The resultant deletion mutants displayed completely different phenotypes compared to the wild-type strain; they had different colony morphology and were no longer able to produce palmarumycins or melanin, thus confirming the involvement of iPKS in the biosynthesis of palmarumycins and melanin in Lophiotrema sp. F6932.